2-Phenylacetic acid-(E,E)-4,4 `-(hydrazinediylidene)dipyridine(2/1) - Arman, H.D.; Kaulgud, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the title co-crystal, C(12)H(10)N(4)center dot 2C(8)H(8)O(2), comprises a single molecule of 2-phenylacetic acid and half a molecule of 4-pyridinealdazine as this is situated about a centre of inversion. Molecules are connected into a three component aggregate via O-H center dot center dot center dot N hydrogen bonds. As the carboxylic acid group is almost normal to the plane through the benzene ring to which it is attached [C-C-C-C = 93.7 (3)degrees], and the 4-pyridinealdazine molecule is planar (r.m.s. deviation of the 16 non-H atoms = 0.010 angstrom), the overall shape of the aggregate is that of an extended chair. In the crystal packing, layers of three component aggregates stack along the c axis.